Ethics and radiological protection - Eggermont, Gilbert; Feltz, Henri (Louvain-la-Neuve, 2007)
"The International Commission on Radiological Protection (ICRP) is recommending measures to guarantee the health of the public exposed to ionising radiation. During the last years, ICRP proposed fundamental changes in its protection approach. What is at stake in this evolution? What is the ethical dimension of radiological protection and how can we frame the process options of ICRP within ethical theories? The ICRP evolution is here analysed from different standpoints. The three successive approaches of radiological protection - justification, optimisation and limits - are focused on ethical aspects by physicists, biologists, engineers, medical physicians, philosophers, ethicists, psychologists and economists. These approaches also take place in the context of precaution and intergenerational responsibility. Recent tendencies in ICRP were paying less attention to justification and optimisation while decreasing the status of limits. The authors express convergences in their concern for a degradation of this unique system of protection based on the precautionary ALARA principle. The hierarchy and complementarities of the triple system of radiological protection are pointed out to be crucial both from ethical and political points of view. "